Differentiation of Imported and Local Rice using Terahertz Time-Domain Spectroscopy (THz-TDS) - Siti Norsyafiqah; Awang, Noor Azura (Enhanced Knowledge in Sciences and Technology, 2026)
Accurate authentication of rice origin is critical for ensuring food quality and market integrity. This study investigates the feasibility of differentiating between imported (Thai Jasmine, Indian Basmathi) and local (Selangor, Kelantan) rice varieties using Terahertz Time-Domain Spectroscopy (THz-TDS). Transmission-mode measurements were conducted on powdered rice samples over the frequency range of 0.1 THz to 3.0 THz. The extracted frequency-domain data revealed distinct absorbance profiles for each variety, attributed to variations in compositional and structural properties. To evaluate the discrimination capability of the system, Principal Component Analysis (PCA) was employed on the spectral data. The PCA results demonstrated clear clustering and separation between imported and local rice samples, confirming the method’s effectiveness. These findings establish THz-TDS, combined with multivariate analysis, as a promising rapid and non-destructive technique for rice origin verification and food safety applications.